2022
DOI: 10.1371/journal.pone.0262884
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Kaempferia parviflora extracellular vesicles, a nanomedicine candidate

Abstract: Plant-derived extracellular vesicles (EVs) are a promising candidate for nanomedicine delivery due to their bioactive cargos, high biocompatibility to human cells, biodegradability, low cytotoxicity, and potential for large-scale production. However, the research on EVs derived from medicinal plants is very limited. In this study, Kaempferia parviflora extracellular vesicles (KPEVs) were isolated by differential and sucrose density gradient centrifugation, and their size, morphology, and surface charge were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…A study on vesicles extracted from Kaempferia parviflora rhizomes reported similar results: that −20 °C and −80 °C conditions effectively preserved the properties of samples, such as size, shape, surface charge, and fatty acid content after 8 weeks, compared to 4 °C and room temperature conditions. Repeated freeze-thaw cycles led to enlarged vesicle sizes and decreased surface potentials [ 74 ]. Another group showed that ginger-derived nanovectors maintained their sizes and charges after storage for 25 days at 4 °C in pH 7.4 buffer [ 82 ].…”
Section: Characterization Of Pdvsmentioning
confidence: 99%
“…A study on vesicles extracted from Kaempferia parviflora rhizomes reported similar results: that −20 °C and −80 °C conditions effectively preserved the properties of samples, such as size, shape, surface charge, and fatty acid content after 8 weeks, compared to 4 °C and room temperature conditions. Repeated freeze-thaw cycles led to enlarged vesicle sizes and decreased surface potentials [ 74 ]. Another group showed that ginger-derived nanovectors maintained their sizes and charges after storage for 25 days at 4 °C in pH 7.4 buffer [ 82 ].…”
Section: Characterization Of Pdvsmentioning
confidence: 99%
“…Chemical methods typically involve the use of chemicals, which may be harmful to humans under certain conditions ( Karimi-Maleh et al, 2021 ). Due to these limitations, recent studies typically focus on biological synthetic methods due to their non-toxicity, cheap, and environmentally friendly nature ( Zhang et al, 2016 ; Nemidkanam and Chaichanawongsaroj, 2022 ). Plants are a major source of different types of phytochemicals with numerous biomedical applications and the extracts are used to treat various diseases.…”
Section: Alternative Therapeutic Approaches and Strategies For Multid...mentioning
confidence: 99%
“…Metal-free PDNPs are environmental friendly, toxic chemical free, cheap, and energy serving ( Kharissova et al, 2019 ; Surendran et al, 2021 ). The potential to derive metal-free NPs with medicinal properties from plants has gained more attention worldwide ( Zhang et al, 2016 ; Saravanan et al, 2021 ; Surendran et al, 2021 ; Liu et al, 2022 ; Nemidkanam and Chaichanawongsaroj, 2022 ). Liu et al (2022) reported the therapeutic ability of metal-free PDNPs on gut microbiota while Xiao et al (2018) highlighted the therapeutic efficacy of metal-free NPs synthesized from 11 edible fruits and vegetables.…”
Section: Alternative Therapeutic Approaches and Strategies For Multid...mentioning
confidence: 99%
“…The EVs isolated from Kaempferia parviflora (KPEVs) had the attractive ability to antagonize tumorigenesis. The engineered KPEVs were stably absorbed into the gastric adenocarcinoma (AGS) cells, leading to the suppression of cell viability in a dose-dependent manner [ 60 ]. Other interesting findings were the identification of exosome-like nanotherapeutics from tea flowers [ 61 ] and tea leaves [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the intrinsic properties of isolated PDEVs are subject to change with some physical parameters, including pH values, temperature, and other processing factors [ 3 , 15 ]. Under a simulated stomach condition, the PDEVs have the potential to resist gastric digestion and maintain high stability [ 60 ]. Unfortunately, at the moment, few studies have specifically investigated the effect of the environment on the structural integrity and bioactivity of PDEVs [ 109 ].…”
Section: Introductionmentioning
confidence: 99%